Response surface methodology as a tool to study the removal of amido black dye from aqueous solution using anionic clay hydrotalcite / Yamin Yasin, Nur Syahirah Abdul Latif and Abdul Hafiz Abdul Malik - Yasin, Yamin; Abdul Latif, Nur Syahirah; Abdul Malik, Abdul Hafiz (Research Management Institute (RMI), 2010)
Anionic clay hydrotalcite was used as an adsorbent to remove amido black dye from aqueous solutions. Response surface methodology (RSM) based on a jive-level, four-variable Central Composite Rotatable Design (CCRD) was employedto evaluate the interactive effects ofvarious optimization parameters. The parameters were contact time (6-10 hrs), solution pH (4-8), adsorbent dosage (200-600 mg) and dye concentration (50-100 mg//). Simultaneously increasing contact time, initial concentration andamount ofadsorbent dosage increased the quantity ofamido black dye removed. The optimum conditions derived via RSM for the reaction were a reaction time of 8.48 hrs, a concentration of58.09 mg/l, an adsorbent dosage of431.24 mg/L anda solution pHof6.27. The experimental percentage removal was 85.55 % under optimum conditions, which compares well with the maximum predicted value of 87.95 %.